2019
DOI: 10.1007/s00268-019-05135-3
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Pelvic Lymph Node Metastases in Rectal Cancer: A Systematic Review

Abstract: Background Synchronous lateral pelvic lymph node (LPLN) involvement occurs in a significant number of patients with rectal cancer. The aim of this study is to determine the rate of LPLN metastases in rectal cancer patients with LPLN suspicious for metastases (LPLNSM) on pretreatment imaging, treated with neoadjuvant chemoradiotherapy (nCRT). Additionally, the influence of LPLN responsiveness to nCRT as determined by post-nCRT restaging scan was investigated. Methods A systematic review was conducted to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…The efficacy of NCRT in sterilizing pelvic sidewall nodes has been studied extensively. A recent systematic review and meta‐analysis 29 reported that between 25 and 85 per cent of persistent clinically suspicious pelvic sidewall nodes following NCRT contained pathologically proven metastasis, and 20 per cent of radiologically responsive nodes contained metastases. The longer‐term significance and oncological outcomes were not considered in this review.…”
Section: Highly Selective Therapeutic Lateral Pelvic Node Dissection mentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of NCRT in sterilizing pelvic sidewall nodes has been studied extensively. A recent systematic review and meta‐analysis 29 reported that between 25 and 85 per cent of persistent clinically suspicious pelvic sidewall nodes following NCRT contained pathologically proven metastasis, and 20 per cent of radiologically responsive nodes contained metastases. The longer‐term significance and oncological outcomes were not considered in this review.…”
Section: Highly Selective Therapeutic Lateral Pelvic Node Dissection mentioning
confidence: 99%
“…An RCT 44 comparing TME with and without LPND after NCRT is recruiting patients, although concerns exist about the method of randomization before restaging MRI, which may lead to overtreatment of some patients and undertreatment of others 29 . This may influence recruitment and highlights the difficulty in conducting randomized trials in an ever‐changing scientific background.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…In contrast, the place of LLND remains a matter of controversy between Eastern and Western surgical guidelines (7)(8)(9)(10)(11)(12). The main conceptual difference is the fact that the lateral pelvic lymph nodes are considered as localized disease in Japanese clinical practice, whereas the West treats them as systemic disease (13)(14)(15). For this reason, in Japan, prophylactic LLND is always performed in patients with stage II/III lower rectal cancer, whereas in the West, chemoradiotherapy (CRT) is routinely performed, thus generally avoiding a more invasive surgical approach (16).…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled trial of 51 patients by Nagawa et al 27 neoadjuvant radiation before surgery with EL did not improve disease‐free survival or recurrence rates, supporting neoadjuvant therapy can be employed as an alternative to EL. It is likely both a neoadjuvant treatment strategy with TME and TME plus EL either sterilizes or removes RLPN disease to clear the circumferential resection margin, which is supported by their equivocal oncologic outcomes 28 …”
Section: Discussionmentioning
confidence: 99%